Integration of STEM and Higher-Order Thinking Skills in Physics Learning: A Bibliometric Review and Practical Implications in Secondary Schools - Isna'atul Rizqi Kusumawardani (PT. AVID MEDIA INDONESIA, 2025)
This study aims to examine the integration of the Science, Technology, Engineering, and Mathematics (STEM) approach and Higher-Order Thinking Skills (HOTS) in physics learning in secondary schools through bibliometric review and literature analysis. This study uses a qualitative research method with a systematic literature review approach to relevant scientific publications over the past decade. The results of the study indicate a significant increase in research linking the implementation of STEM with the development of HOTS, especially in project-based learning models and scientific inquiry. The integration of both has proven effective in improving students' analytical, evaluative, and creative abilities through contextual and collaborative learning experiences. In addition, successful implementation is highly dependent on teachers' pedagogical competence, curriculum readiness, and educational policy support that supports innovation in science learning. This study provides practical implications for the development of interdisciplinary curricula, teacher professional training, and strengthening students' scientific literacy. Conceptually, the results of this study confirm that STEM–HOTS integration is not only a pedagogical strategy, but also an educational paradigm that fosters scientific, adaptive, and creative thinking skills as preparation for facing the challenges of the digital era.